(untitled) (Ustozlar uchun, 2026)
This article examines the methodological foundations of organizing spiritual, educational, and professional activities in technicums. Modern vocational education institutions are responsible not only for providing students with professional knowledge and practical skills but also for fostering their moral values, social responsibility, and personal development. Well-planned events contribute significantly to the formation of students’ competencies, civic consciousness, cultural awareness, and professional identity. The study highlights the importance of integrating spiritual and educational activities with vocational training to create a holistic learning environment. Various methodological approaches, principles, and strategies for organizing effective events in technicums are discussed. The article emphasizes that systematic and purpose-oriented activities play a crucial role in preparing competent, ethical, and socially active specialists for contemporary society.